Does the housing market react to new information on school quality? - Jon H. Fiva; Lars J. Kirkebøen (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper analyzes housing market reactions to the release of previously unpublished information on school quality. Using the sharp discontinuity in the information environment allows us to study price changes within school catchment areas, thus controlling for neighborhood unobservables. We find a substantial housing market reaction to publication of school quality indicators, suggesting that households care about school quality, and may be willing to pay for better schools. The publication effect is robust to a number of sensitivity checks, but does not seem to be permanent as prices revert to prepublication levels after two to three months. We discuss this reversion in relation to the literature on behavioral finance and the concept of limited attention.
Keywords: I21; I28; R21; R23; 330; valuation of school quality; hedonic methods; price reversion; Immobilienmarkt; Schule; Schulauswahl; Dienstleistungsqualität; Bewertung; Immobilienpreis; Theorie